2018
DOI: 10.1111/bjhp.12323
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of physiotherapist’s delivery of behaviour change techniques within the SOLAS feasibility trial

Abstract: Delivering the SOLAS intervention BCTs with high fidelity was not feasible. The assessment of partial delivery of BCTs provided greater insight into the techniques that should be removed from the protocol or that may require further training. Complex interventions should consider a list of 'core' or mandatory BCTs alongside 'optional' BCTs, depending on the target behaviour, and the needs of individual participants. Statement of contribution What is already known on this subject? BCTs are the smallest active c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 60 publications
3
27
0
Order By: Relevance
“…These ndings are consistent with previous literature and suggest sustained increases in autonomous motivation may be required for behaviour change [51][52]. Although PTs underwent training and were deemed competent to deliver SOLAS within the feasibility trial, they struggled to effectively utilise speci c strategies related to goal setting [25][26]. This is noteworthy as a collaborative goal-setting process between a health care professional and patient is likely to be important in increasing and sustaining a patient's autonomous motivation and competence for the particular behaviour [53][54][55].…”
Section: Solas Process Model Of Behaviour Changesupporting
confidence: 87%
See 2 more Smart Citations
“…These ndings are consistent with previous literature and suggest sustained increases in autonomous motivation may be required for behaviour change [51][52]. Although PTs underwent training and were deemed competent to deliver SOLAS within the feasibility trial, they struggled to effectively utilise speci c strategies related to goal setting [25][26]. This is noteworthy as a collaborative goal-setting process between a health care professional and patient is likely to be important in increasing and sustaining a patient's autonomous motivation and competence for the particular behaviour [53][54][55].…”
Section: Solas Process Model Of Behaviour Changesupporting
confidence: 87%
“…A comprehensive assessment of the delity of intervention delivery, another key component of feasibility has been reported separately [25][26][27].…”
Section: Aims and Objectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Tailoring of adherence interventions in the literature is, however, currently uncommon-this has been illustrated in a recent meta-analysis of 771 adherence interventions delivered to adult patients (18 years+) which found only nine studies that reported individual-level tailoring [6]. Keogh et al [25] have also recently advocated for the inclusion of 'core' and 'optional' BCTs in complex interventions, following their recent feasibility study that found that a physiotherapistled self-management group intervention containing a large number of BCTS (n = 31) was delivered with low to moderate fidelity. This type of tailoring could be particularly useful in contexts where there are high levels of heterogeneity amongst patients and in busy healthcare environments where time restrictions limit the duration of sessions/appointments.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…These can be conceptualized as compositional/structural features forming items of the index and functional/process features forming the anchors to quantify each item. While studies have previously developed methods to characterize the content of BS using the behaviour change techniques (BCTs) taxonomies and BCT associations with outcomes , these limit ratings to the delivery process and their predictive value for outcomes. The extent to which fidelity of delivery of a BS intervention influences smoking cessation outcomes remains unclear.…”
Section: Introductionmentioning
confidence: 99%